AORTIC THROMBOSIS – A SINGULAR MANIFESTATION OF CROHN DISEASE - LOPES, Catarina (2023)
Aortic thrombosis (AT) is an unusual extraintestinal manifestation of Crohn’s disease (CD). We present a case of a male submitted to supracondylar amputation of the right lower limb due to irreversible acute ischemia. During the post-operative period, he developed signs of contralateral limb ischemia and performed complementary diagnostic tests which revealed a thrombus in the aortic bifurcation, a terminal ileum thickening, compatible with CD, and a polypoid lesion in the distal rectum. After patient staging and colorectal surgery, the complete resolution of AT was demonstrated.